(untitled) (International Journal of Innovative Technologies in Economy, 2022)
The article analyzes scenario approaches to the development of the energy system of the world, as well as agreeing on the positive and negative sides, and proposes practical mechanisms to improve the efficiency of the energy system of the NKR. Modern models of energy development are presented in the article, of which 6 are mainly used. The necessity of using the SCANNER model to improve the efficiency of the energy system of the NKR is especially emphasized, because it is as close to reality as possible.